Determinanty strategicznego zarządzania kosztami logistyki w łańcuchu dostaw - Piechota, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The logistic processes made real in a supply chain require to bear some costs. It is more important to use decision cost accounting, which gives the possibility to make the decisions for rationalization those costs. This elaboration shows the factors which have influence to the efficacy of strategic cost management in a supply chain. The purpose of this elaboration is to underline the importance of minimalization of logistic costs in a supply chain as an important factor of effectiveness growth of all its partners of supply chain. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 332-339